Exposure assessment of Listeria monocytogenes and biofilm formation in ready-to-eat cheese - Lee, Hai Yen (2011)
Cheese has been implicated in many different outbreaks of human listeriosis worldwide through consumption of contaminated cheese that occurs at farm and processing levels. The risk involved in consumption of a contaminated cheese can be evaluated through exposure and risk assessment. A total of 214 samples of cheeses were obtained from various point of entry (importing ports) in Malaysia as well as cheese from retail stores in five different states were assessed for prevalence and enumeration of L. monocytogenes. The concentration of L. monocytogenes in the samples were applied to model the exposure assessment on the contaminated food samples obtained from the entry point to the processing factory, and from the factory to the consumer’s home prior consumption. Different scenarios were included in the exposure assessment model to show the effect of temperature, pH and water activity in the growth of L. monocytogenes. In previous studies, persistence and contamination of food products in the food processing environment may be attributed to the biofilm formation by L. monocytogenes. It was found that biofilm formation occurs at high level of sodium chloride, different temperatures over a period of 60 h. At 4°C, biofilm formation occurs more rapidly. The cross contamination of L. monocytogenes can occur from formation of biofilm on food grade stainless steel to plastic wrappers through contact. The transfer of L. monocytogenes from stainless steel to polypropene plastic wrappers showed that biofilm and colonies of L. monocytogenes can be transferred through contact surface, regardless of weight applied on the surface type. This showed a steady contamination rate in the processing factory when biofilm is found on the surface. The removal of biofilm and colonies of L. monocytogenes using laboratory designed cleaning-in-place (CIP) system using water, commercial detergent and bleach, showed that removal of colonies was effective using the commercial detergent and bleach (P>0.05) and has a log reduction of 1 to 1.5 log cfu/ml. The design of CIP did not remove the biofilm on the surface of stainless steel using water and detergent, but bleach concentration of 10% (5.55% active compound of sodium hypochlorite) were able to significantly reduce the density of biofilm on the stainless steel surface. The preliminary risk assessment showed that worst case scenario of listeriosis are highest in immunocompromised individuals and can be significantly reduced through intervention strategies such as the CIP cleaning for removal of biofilm from the stainless steel surface and reducing the cross contamination of food products.